European consensus for starting and stopping enzyme replacement therapy in adult patients with Pompe disease: a 10-year experience - A. T. van der Ploeg; M. Ую Kruijshaar; A. Toscano; P. Laforet; C. Angelini; R. H. Lachmann; S. I. Pascual Pascual; M. Roberts; K. Rosler; T. Stulnig; P. A. van Doorn; P.Y. K. Van den Bergh; et al. (Нервно-мышечные болезни)
.